Computational study of the presence of defects in semiconducting polymers on exciton formation - Correia, Helena M. G. (2011)
Although semiconducting polymers are very attractive to be used in optoelectronic devices due to their molecular structure, they are not pristine semiconductors. After deposition it is possible to find out several structural and chemical defects, with different origins, that strongly influence exciton dynamics since they create deep energetic sites, where excitons can migrate leading to their quenching or reducing exciton diffusion length. By using a self-consistent quantum molecular dynamics method we performed a computational study to understand the influence of well-known polymer defects on excitons dynamics. Our results show that these defects influences mainly intramolecular exciton localization and exciton energy.